'Aulophyseter' rionegrensis (Cetacea: Odontoceti: Physeteroidea) from the Miocene of Patagonia (Argentina): a reappraisal. Issue 4 (11th December 2020) - Paolucci, Florencia; Fernández, Marta S; Buono, Mónica R; Cuitiño, José I
Abstract: The giant sperm whale ( Physeter macrocephalus ) and the dwarf ( Kogia sima ) and pygmy ( Kogia breviceps ) sperm whales represent the only three extant species of physeteroids. This group has diversified during the Miocene, and the Miocene marine sediments of Patagonia (Argentina) hold one of the most important fossil records of physeteroids. In particular, ' Aulophyseter ' rionegrensis (Gran Bajo del Gualicho Formation, Miocene), described based on two subcomplete skulls nearly a century ago, has been a problematic taxon because its generic assignation has been questioned in different works. Besides, recent phylogenetic analyses have also failed to recover the putative congeneric sister-group relationship between ' A. ' rionegrensis and A. morricei (the type species). In this contribution, we re-describe ' A. ' rionegrensis, evaluate its phylogenetic position and provide a taxonomic review of Aulophyseter . A detailed morphological comparison between ' A. ' rionegrensis and A. morricei reveals several anatomical differences between them. Phylogenetic analyses recover ' A. ' rionegrensis as a crown physeteroid, nested within Physeteridae, but not closely related to A. morricei . We provide the new generic name Cozzuoliphyseter gen. nov. for its reception. A preliminary re-assessment of material previously referred to Aulophyseter indicates that A. mediatlanticus, and also historical material of A. morricei, need to be reviewed.